2012
DOI: 10.1080/10476210.2011.641528
|View full text |Cite
|
Sign up to set email alerts
|

Community-based field experiences in teacher education: possibilities for a pedagogical third space

Abstract: Abstract:The present article discusses the importance of community-based field experiences as a feature of teacher education programs. Through a qualitative case study, prospective teachers' work with homeless youth in an after-school initiative is presented. Framing community-based field experiences in teacher education through "third space" theory, the article discusses the value that such experiences have for prospective teachers' learning. The goals of the article align with the commitment to preparing a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 28 publications
(23 reference statements)
0
38
0
3
Order By: Relevance
“…These alternative clinical experiences are beneficial early on in teacher education before expectations and stereotypes of alternative learners become solidified and harder to overcome (Bennett, 2012;Hallman, 2012;Kumar & Hamer, 2012). While all teacher education programs include coursework on multicultural education, the results from this study have shown that simply providing meaningful and interactive clinical experiences early on in a program can be beneficial.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These alternative clinical experiences are beneficial early on in teacher education before expectations and stereotypes of alternative learners become solidified and harder to overcome (Bennett, 2012;Hallman, 2012;Kumar & Hamer, 2012). While all teacher education programs include coursework on multicultural education, the results from this study have shown that simply providing meaningful and interactive clinical experiences early on in a program can be beneficial.…”
Section: Discussionmentioning
confidence: 73%
“…Experiences such as these can help pre-service teachers to not only identify the individual needs of their students, but also to be able to respond to them effectively (Lawrence & Butler, 2010). These kinds of alternative, communitybased experiences act as the 'third space' of teacher education and allow for pre-service teachers to dismantle their understanding of what it means to teach all students effectively (Hallman, 2012). This kind of 'third space' can also serve to bring the knowledge of practicing teachers together with the academic knowledge of the college classroom and create unique and meaningful opportunities for pre-service teachers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…So having that conversation at the university and then seeing it in practice was really cool. [Interview, Ray, 2012] The opportunity to teach in an after-school setting provided a way to get to know youth of colour who, although they were struggling academically, brought rich cultural knowledge to the science practice-resulting in transformative learning for Ray (Hallman, 2012). He gained a better understanding of the cultural processes of learning and what it means when children and teachers construct the curriculum together (Jurow et al, 2012).…”
Section: Ways To Engage Student Teachers In Transformative Learningmentioning
confidence: 99%
“…The challenge for a teacher education program, then, is to engage with these visions of schools and youth in underserved and ethnically diverse communities and help student teachers develop other ways of seeing and relating to youth of colour (Coffey, 2009;Hallman, 2012). Ray's story offers another illustration of that process:…”
Section: Ways To Engage Student Teachers In Transformative Learningmentioning
confidence: 99%